The Tangibilization of Indigenous Dances and the Rehearsal of a Similarity Model for Quantitative Analysis of Movement - Jorge Poveda; Rory Fewer; Benedikte Wallace (Revista de Humanidades Digitales)
This article explores several tools of varied affordability within the field of computer-based technologies of human movement recognition as a means of responding to the current lack of protection extended to Indigenous dances. Following a general theoretical overview of new technologies developed to process human movement, including motion capture, video visualization, and computer vision, this paper offers an investigation into the practical applications of such technology when applied to dance. The Movement Similarity Project at the University of Oslo’s RITMO Centre is explored as a case study, in which motion-capture technology has been utilized to measure and quantify the degree of similarity between different dance recordings. The possibilities, limitations, and future directions of these technologies are evaluated according to their ability to safeguard Indigenous dances.